2022
DOI: 10.3390/genes13091526
|View full text |Cite
|
Sign up to set email alerts
|

SR Protein Kinases Regulate the Splicing of Cardiomyopathy-Relevant Genes via Phosphorylation of the RSRSP Stretch in RBM20

Abstract: (1) Background: RNA binding motif 20 (RBM20) regulates mRNA splicing specifically in muscle tissues. Missense mutations in the arginine/serine (RS) domain of RBM20 lead to abnormal gene splicing and have been linked to severe dilated cardiomyopathy (DCM) in human patients and animal models. Interestingly, many of the reported DCM-linked missense mutations in RBM20 are in a highly conserved RSRSP stretch within the RS domain. Recently, it was found that the two Ser residues within this stretch are constitutivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…Notably, all but three of the SRPK3/TTN families did not present cardiac involvement. Speculatively, abnormal RBM20 phosphorylation by SRPK3 in the heart would be overcome by ubiquitously expressed kinases, as shown recently for cdc2-like kinases (CLKs) and protein kinase B (AKTs) 25 and supported by our in vitro phosphorylation assay. Although RBM20 has not yet been associated with skeletal muscle disease, it has been shown to be DE across different skeletal muscles, where it regulates Z-band and M-band TTN splicing 48 .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Notably, all but three of the SRPK3/TTN families did not present cardiac involvement. Speculatively, abnormal RBM20 phosphorylation by SRPK3 in the heart would be overcome by ubiquitously expressed kinases, as shown recently for cdc2-like kinases (CLKs) and protein kinase B (AKTs) 25 and supported by our in vitro phosphorylation assay. Although RBM20 has not yet been associated with skeletal muscle disease, it has been shown to be DE across different skeletal muscles, where it regulates Z-band and M-band TTN splicing 48 .…”
Section: Discussionsupporting
confidence: 75%
“…We hypothesized that RBM20 might be a phosphorylation substrate of SRPK3 and the mediating link between SRPK3 and titin, as previously shown for SRPK1 (ref. 25 ). To investigate this, we cotransfected an RBM20 reporter (RBM20 517–664 -V5) into 293T cells with or without a GFP-SRPK3 construct.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to TNPO3 , we selected other hits with less significant FDR scores ( CLDN14 , GALE , ADAMTS16 , SLC29A2 , CEBPB , UBQLNL , TRIM33 , PMM2 , TRIM24 , IPPK , XPO6 , Supplementary Fig. 5e ) and based on prior knowledge about their relevance for RBM20 function 18 , 36 , 37 ( TTN , AKT2 , SPRK1 , CLK1 , LMNA ). We tested these potential positive hits by constructing single-gene KOs in HeLa cells and assessing their impact on RBM20-WT localization by ICS and fluorescence microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that the binding of TNPO3 to its cargo can be phosphorylation-dependent 40 42 or independent 46 . In the case of RBM20, serine residues in the RS domain are normally phosphorylated 26 , 35 , 37 , 44 , however, phosphomimetic amino acid substiutions do not rescue the localization phenotype 26 . Importantly, both pooled and individual CRISPR KOs of kinases AKT2 , CLK1 , and SPRK1 —previously shown to phosphorylate RBM20 37 —did not impact RBM20 localization (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have increasingly focused on the role of post-translational modifications, especially phosphorylation, in AS regulation [ 41 43 ]. For example, AMP-activated protein kinase (AMPK) and SR protein kinase 1 (SRPK1) phosphorylate SRSF1 [ 44 , 45 ]; PPM1G phosphorylates SRSF3 [ 46 ]; CDK11 phosphorylates SF3B1 [ 47 ]; oncogenic KRAS regulates SFs phosphorylation [ 48 ]; SR protein kinase regulates the phosphorylation of the RSRSP stretch in RBM20 [ 49 ]; ERK2 regulates the phosphorylation of Thr113 and Thr118 [ 50 ]; and the C-terminal domain of RNA polymerase II (Pol II CTD) is also phosphorylated [ 51 ]. These phosphorylation events in SFs and RBPs have various regulatory effects on AS.…”
Section: Discussionmentioning
confidence: 99%